2009
DOI: 10.1088/0031-9155/54/18/004
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced radiotherapy: feasibility and characteristics of the physical absorbed dose distribution for deep-seated tumors

Abstract: Radiotherapy using kilovoltage x-rays in conjunction with contrast agents incorporated into the tumor, gold nanoparticles in particular, could represent a potential alternative to current techniques based on high-energy linear accelerators. In this paper, using the voxelized Zubal phantom in conjunction with the Monte Carlo code PENELOPE to model a prostate cancer treatment, it is shown that in combination with a 360 degrees arc delivery technique, tumoricidal doses of radiation can be delivered to deep-seated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Furthermore, a commercial kilovoltage X-ray unit with the ability to deliver intensitymodulated radiation is unlikely to be developed. Other studies examined the feasibility of using 150-kVp radiation to treat prostate cancers loaded with a uniform distribution of 1% gold [63]. While it was possible to deliver 72 Gy to the prostate without exceeding tolerance doses to organs at risk (including rectum, bladder, Figure 5.…”
Section: Monte Carlo Modelling Studiesmentioning
confidence: 99%
“…Furthermore, a commercial kilovoltage X-ray unit with the ability to deliver intensitymodulated radiation is unlikely to be developed. Other studies examined the feasibility of using 150-kVp radiation to treat prostate cancers loaded with a uniform distribution of 1% gold [63]. While it was possible to deliver 72 Gy to the prostate without exceeding tolerance doses to organs at risk (including rectum, bladder, Figure 5.…”
Section: Monte Carlo Modelling Studiesmentioning
confidence: 99%
“…CERT has been studied by various authors mostly from MC computational and treatment planning standpoints. [30][31][32][33][34][35][36][37][38][39][40] In CERT studies, macroscopic dose enhancement and beam attenuation are computed based on hypothetical planning CT with and without the contrast. Because contrast uptake is typically passive (via tumour microvasculature), endothelial cells are more likely to experience higher dose enhancement than the tumour cells, which are farther away from the microvessels with the contrast.…”
Section: Macroscopic Dose Enhancement and Dose At High-z Interfacesmentioning
confidence: 99%
“…Given that the Oraya Therapy system delivers kV energy x-rays and specifically targets the choroidal neovasculature, Ngwa et al proposed and demonstrated in a theoretical study that GNPs would significantly enhance kV stereotactic radiosurgery for neovascular AMD [100], representing a departure from previous GNRT work, mainly focused on potential cancer therapy applications [42,101,154156]. Justification for pursuing such a targeted RT with GNPs for wet AMD also comes from studies showing that nanoparticles can be specifically targeted to the AMD choroidal neovasculature [143,157,158].…”
Section: Emerging Gnrt Modalitiesmentioning
confidence: 99%